PENGARUH FAKTOR HUMAN CAPITAL PADA PENGANGGURAN GOLONGAN USIA MUDA INDONESIA TAHUN 2019 - Sahira, Laras; Bintoro, Nugroho Suryo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Youth are one of the most important assets in strengthening a country's socio-economic development. In addition to their large number, youth are also the most active and productive resources. But in reality, youth are the one who hold the highest rate of unemployment in Indonesia. Using binary logistic regression model, this study will try to identify factors that influence the chances of labor force age 15-24 to become unemployed. The data used are from Indonesia’s labor force survey known as Survei Angkatan Kerja Nasional (SAKERNAS) in 2019. Results of the study show that human capital in the form of education and training, as well as gender and marital status have significant impact on employment probabilities of youth in Indonesia. Whereas geographical location between urban and rural area does not have a significant effect on their employment status. Therefore, it is necessary for the government and policy makers to take into account these factors in designing and creating unemployment intervention policies in Indonesia.